2016
DOI: 10.1182/blood-2015-09-671834
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity transplantation for lymphomas using haploidentical related donors vs HLA-matched unrelated donors

Abstract: Key Points• Risk of grade III-IV acute and chronic GVHD is significantly lower with haploidentical compared with URD transplantation.• Relapse risk, NRM, PFS, and OS was similar in haploidentical transplants compared with unrelated donor transplants.We evaluated 917 adult lymphoma patients who received haploidentical (n 5 185) or HLAmatched unrelated donor (URD) transplantation either with (n 5 241) or without antithymocyte globulin (ATG; n 5 491) following reduced-intensity conditioning regimens. Haploidentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
150
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 253 publications
(175 citation statements)
references
References 35 publications
(70 reference statements)
23
150
1
1
Order By: Relevance
“…66,[80][81][82][83][84] In 475 patients with a variety of hematologic malignancies, Bashey et al showed matched sibling, optimally (10 of 10 HLA allele) matched unrelated donor, and haploidentical transplants all had similar 2-year disease-free survival (ie, 56% vs 50% vs 54%). 80 In 459 patients, Raiola et al showed 4-year disease-free survival was 43% after haploidentical transplantation, 32% after matched sibling transplantation, 36% after matched unrelated donor transplantation, 34% after mismatched unrelated donor transplantation, and 33% after unrelated cord blood transplantation.…”
Section: Haploidentical Vs Matched Hematopoietic Transplantationmentioning
confidence: 99%
“…66,[80][81][82][83][84] In 475 patients with a variety of hematologic malignancies, Bashey et al showed matched sibling, optimally (10 of 10 HLA allele) matched unrelated donor, and haploidentical transplants all had similar 2-year disease-free survival (ie, 56% vs 50% vs 54%). 80 In 459 patients, Raiola et al showed 4-year disease-free survival was 43% after haploidentical transplantation, 32% after matched sibling transplantation, 36% after matched unrelated donor transplantation, 34% after mismatched unrelated donor transplantation, and 33% after unrelated cord blood transplantation.…”
Section: Haploidentical Vs Matched Hematopoietic Transplantationmentioning
confidence: 99%
“…[1][2][3][4][5][6] outcomes for haplo T-cell-replete transplantation with PT-Cy, donor prioritization strategies are extrapolated from HLA-matched related and unrelated donor transplantation. 7 The Baltimore group's selection algorithm for haplo donors incorporates donor-specific antibodies, donor-recipient ABO match, donor age, donor sex, and cytomegalovirus (CMV) serostatus match.…”
Section: Introductionmentioning
confidence: 99%
“…11 Although single-institution studies 12,13 have shown encouraging results of Haplo-HCT with PT-Cy in lymphoma, and although a recent registry analysis has reported comparable outcomes of Haplo-HCT versus matched URD allo-HCT in patients with lymphoma, 14 it remains unclear whether the greater degree of HLA disparity associated with haploidentical allografts results in higher NRM and inferior survival when compared with MSD-HCT, the established standard for allo-HCT. To address this question, we compared the outcomes of Haplo-HCT against MSD-HCT in patients with lymphoma, using the observational database of the Center for International Blood and Marrow Transplant Research.…”
Section: Introductionmentioning
confidence: 99%